Preserving Digital Footprints: Strategies for Safeguarding Ephemeral Online Data - Balogun, Tolulope (International Journal of Knowledge Content Development & Technology, 2025)
This paper discusses the issues related to ephemeral nature of online data and explores the strategies to safeguard digital heritage, particularly focusing on the nexus between ephemeral online data and web archiving. Document analysis was adopted to select peer-reviewed articles, reports, and publications from reputable academic databases and grey literature sources, covering the period from 2010 to 2024. The research reveals the ephemeral nature of online data, highlighting the challenges it poses for digital heritage preservation. Web archiving emerges as a crucial tool for preserving ephemeral online data, offering opportunities to capture and retain digital content for future generations. Recommendations are provided to address technical, legal, and ethical challenges facing web archiving, emphasizing the importance of interdisciplinary collaboration, increased awareness, and the development of clear digital preservation frameworks that incorporates ephemeral online data. The findings have practical implications for stakeholders involved in digital preservation, including archivists, researchers, policymakers, and technology developers.